Rethinking Transediting - Schäffner, Christina (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
This paper reflects on the terms used in investigating news translation, with a special focus on the term transediting as it was suggested in a paper by Stetting. After a summary of Stetting’s original arguments, some research into news translation is presented, illustrating main methods, findings, and concepts used. The paper presents arguments put forward by various scholars for using or rejecting the term translation for describing the complex processes of translation in the context of mass media and illustrates which alternative terms are used. It is shown that Stetting’s original aim in coining the term transediting was to raise awareness of translation being more than a pure replacement of a source text by an equivalent target text. Transformations as identified in news translation, however, are characteristic of translation more generally. Therefore, the paper finally reflects on whether there is a need to keep the term transediting and whether it has any explanatory power for describing the practices in news translation.